Model-driven engineering of cloud components in MetaMORP(h)OSY. (1st January 2014) - Moscato, Francesco; Amato, Flora; Amato, Alba; Aversa, Rocco
Cloud architecture is established as a standard for services provisioning. Discovering of services is a hard task since several services have to be analysed. The mOSAIC project aims at providing a framework for searching and interfacing services from multiple vendors. Its main component, the cloud agency, provides searching and wrapping features and the management of Services Level Agreements (SLAs). In this scenario, validating services requirements is appealing. Usually users are forced to use SLAs pre-offered by providers that need to reconfigure cloud components in order to meet requests. Model-Driven Engineering (MDE) methodologies allow for requirements verification during all life cycle of systems. They can be exploited in definition of models for cloud components that have to be used and configured in order to fulfil requested service levers. Here, the MetaMORP(h)OSY methodology and framework are introduced and applied to the verification of SLAs in the mOSAIC platform.